2009
DOI: 10.1186/1742-4690-6-94
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and virological analysis of the 18-residue C-terminal tail of HIV-1 integrase

Abstract: Background: The 18 residue tail abutting the SH3 fold that comprises the heart of the C-terminal domain is the only part of HIV-1 integrase yet to be visualized by structural biology. To ascertain the role of the tail region in integrase function and HIV-1 replication, a set of deletion mutants that successively lacked three amino acids was constructed and analyzed in a variety of biochemical and virus infection assays. HIV-1/2 chimers, which harbored the analogous 23-mer HIV-2 tail in place of the HIV-1 seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 67 publications
(90 reference statements)
5
53
0
Order By: Relevance
“…In vitro integration assay was performed as in ref. 38. Taq/Pfu PCR details and other additional information are available in SI Materials and Methods.…”
Section: Human Cd4mentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro integration assay was performed as in ref. 38. Taq/Pfu PCR details and other additional information are available in SI Materials and Methods.…”
Section: Human Cd4mentioning
confidence: 99%
“…We next examined whether uracil-induced DNA structural changes in target DNA might inhibit HIV IN strand transfer. We used an in vitro integration assay in which recombinant HIV IN catalyzes half-site integration (joining of only one strand of dsDNA) of a donor and a target DNA (38). This assay is often used to characterize IN strand transfer activity and assess host factors, such as LEDGF, that influence integration (39).…”
Section: Activity (mentioning
confidence: 99%
“…demonstrated that mutations in the IN gene, including deletion mutants, influence many other stages of viral replication in addition to integration. This pleiotropic effect of IN is characterized by defects in uncoating, reverse transcription, nuclear import, viral gene expression, virion precursor protein processing, and virion morphology (Shin et al, 1994;Engelman et al, 1995;Masuda et al, 1995;Bukovsky & Gottlinger, 1996;Leavitt et al, 1996;Nakamura et al, 1997;Engelman, 1999;Tsurutani et al, 2000;Lu et al, 2004;Dar et al, 2009;Briones et al, 2010). However, the mechanisms for these pleiotropic effects of the IN gene are still poorly understood.…”
Section: Integration Reactionmentioning
confidence: 99%
“…The total amount of synthesized viral cDNA in knockdown cells with both viral vectors was increased by 1.8-to 2-fold the amount in control cells at 10 h, suggesting that reverse transcription was partly abrogated by YY1. Previously, it was shown that the C-terminal region of HIV-1 IN binds to reverse transcriptase, and mutations in the C-terminal region of HIV-1 and MoMLV INs hamper the reverse transcriptase activity (8,27,58,62). Since YY1 binds to the C-terminal region of the MoMLV IN, it is possible that YY1 may affect reverse transcriptase activity.…”
Section: Physical Interaction Of Ins With Yy1mentioning
confidence: 99%
“…After standing at 4°C for 30 min, 1.2 g of target DNA plasmid (1 to 2 l, pBluescript II KS Ϫ ; Stratagene) was added, and the reaction was started by the addition of concentrated buffer solution at a final concentration of 20 mM 2-(N-morpholino)ethanesulfonic acid (MES) (pH 6.2), 165 mM KCl, 10 mM MnCl 2 , 10 mM DTT, and 10% dimethyl sulfoxide (DMSO) (total volume, 35 l). 8.0], 0.5% SDS, and 100 g/ml proteinase K). After electrophoresis on a 1% agarose gel, integration products were detected by autoradiography.…”
Section: Preparation and Analyses Of Picsmentioning
confidence: 99%